Analyzing EFL Students’ Critical Thinking Through Literary Texts - Br Sembiring, Elita Modesta; Tarigan, Natalia Widya Pasca; Br Tarigan, Merry Susanty; Kuanda, Reynaldi (English Language Teaching Prima Journal (ELT), 2024)
This study examines the role of literary texts in fostering critical thinking among English as a Foreign Language (EFL) students. Employing a qualitative approach, the research utilizes literary analysis and classroom observation to assess how students critically engage with texts. This study was conducted to the students at Akademi Keperawatan Columbia Asia Medan. Results suggest that literary texts significantly enhance critical thinking skills when paired with guided discussion and analytical tasks.